2020
DOI: 10.3390/nu12123766
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Telomeric Repeat–Containing RNA Decreases in Sarcopenia and Increases after Exercise and Nutrition Intervention

Abstract: Sarcopenia is defined as aging-related loss of muscle mass and function. Telomere length in chromosomes shortens with age and is modulated by telomeric repeat-containing RNA (TERRA). This study aimed to explore the impact of aging and sarcopenia on telomere length and TERRA expression, and changes following strengthening exercise and nutrition intervention (supplement of branched-chain amino acids, calcium and vitamin D3) for 12 weeks in the sarcopenic population. Older adults (≥65 years old) were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…Low muscle mass indicated a skeletal muscle mass index less than 7.40 kg/m 2 for men and 5.14 kg/m 2 for women. In the present study, we did not use EWGSOP2 [20] for concern of comparability with other diagnostic algorithm for sarcopenia [21] and consistency with our serial studies [22][23][24].…”
Section: Definition Of Sarcopeniamentioning
confidence: 69%
“…Low muscle mass indicated a skeletal muscle mass index less than 7.40 kg/m 2 for men and 5.14 kg/m 2 for women. In the present study, we did not use EWGSOP2 [20] for concern of comparability with other diagnostic algorithm for sarcopenia [21] and consistency with our serial studies [22][23][24].…”
Section: Definition Of Sarcopeniamentioning
confidence: 69%
“…In a study comparing telomere length between participants with sarcopenia and control participants, the authors found no significant differences in telomere length between groups. 38 In contrast, in patients with sarcopenia, frailty, or both, telomere length was shortened. 39 Although the impact of telomere length on sarcopenia and frailty is not thought to be strong, to evaluate the real effect of telomere shortening on muscle function, measuring telomere length in myocytes and satellite cells, instead of blood cells, is required.…”
Section: Telomere Shorteningmentioning
confidence: 99%
“…US-guided aspiration of ascites is helpful for the determination of its biochemical profile as well as for symptomatic relief. Sarcopenia (decreased muscle mass and function) is prevalent in the aging population [21,22]. In a previous study, thinning of the rectus abdominis, external oblique, and internal oblique muscles was observed on US imaging in 103 middleaged and old-aged healthy women [23].…”
Section: A C C E P T E Dmentioning
confidence: 99%